PERBEDAAN PERSEPSI ANTARA MAHASISWA SENIOR DAN MAHASISWA JUNIOR MENGENAI PROFESI AKUNTAN PADA PROGRAM STUDI S1(PADA MAHASISWA AKUNTANSI UNIVERSITAS WIJAYA KUSUMA SURABAYA) - Dinda Rolesa; Wiwin Wahyuni (CV. Denasya Smart Publisher, 2025)
The accounting profession plays a vital role in the business and economic world as a provider of accurate financial information to support decision-making. In the face of changes in the business environment and technological advances, students' perceptions of this profession are important because they are the future professionals. This study aims to compare the perceptions of senior and junior students in the Accounting Program at Wijaya Kusuma University in Surabaya toward the accounting profession. Differences in perspectives between the two groups are believed to be influenced by academic experience, exposure to the workplace, and understanding of the challenges of the accounting profession. The method used is descriptive comparative with a quantitative approach. Data was collected through questionnaires distributed to first-year and final-year students, then analyzed to identify differences in perceptions. The results show that senior students have more realistic and critical views, while junior students tend to be idealistic and optimistic. These differences are related to the greater internship experience and interaction with practitioners experienced by senior students. These findings emphasize the importance of practical experience and case-based learning in shaping mature perceptions. This study provides valuable insights for curriculum development and career development strategies to prepare graduates to face the dynamics of the accounting profession and strengthen the integration of theory and practice in accounting education